Enhancing Service Quality Through Innovation: A Study of Sucofindo Indonesia's Strategies in Global Competition - Sugiantari, I Gusti Ayu Dwi Ardiani; Merta, I Ketut; Widiantara, I Kadek (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to test the service innovation of Sucofindo Indonesia in improving service quality as an effort to maintain firm sustainability in the era of globalization, using the grand theory of Human resource management and supporting marketing management theory applied theory of service innovation, service quality and firm sustainability. This research method uses an associative quantitative method, and a questionnaire with a population of 102 and a sampling sample of 46 using the slovin formula with four hypotheses and data processing using SPSS Version 24. The results of the study found 1. Service Quality has a positive and significant effect on Firm sustainability, 2. Service Quality has a positive and significant effect on service innovation 3. Firm sustainability has a positive and significant effect on service innovation . 4. Firm sustainability, is able to mediate service quality, against service innovation. The implications of this study produce service quality, service innovation, and firm sustainability of Sucofindo Indonesia are quite moderate and indicate that firm sustainability can mediate service quality in service innovation.